Profile of Prospective Elementary School Teachers’ Ability in Developing Learning Materials Based on the Culturally Responsive Teaching Approach - Feby Inggriyani; Siti Sholiha Nurfaidah; Desti Fatin Fauziyyah (Berkala Ilmiah Pendidikan, 2026)
This study investigates how elementary teacher education (PPG PGSD) students develop instructional materials grounded in the Culturally Responsive Teaching (CRT) framework and analyzes how the five core CRT dimensions are operationalized in their instructional designs. Responding to the limited empirical evidence on the practical enactment of CRT within teacher preparation programs, this study contributes by offering an analytical examination of pre-service teachers’ design competence rather than merely their conceptual understanding. A qualitative descriptive approach was employed involving ten PPG PGSD students. Data were collected through CRT-based instructional material assignments, semi-structured interviews, and rubric-guided assessments. The five CRT dimensions, cultural awareness, culturally relevant curriculum integration, inclusive learning environment, critical consciousness development, and culturally responsive assessment, were translated into explicit analytical indicators to ensure systematic evaluation. Although qualitative in design, percentage scores (average mastery of 89.23%) were incorporated as descriptive support to enhance analytic clarity rather than statistical generalization. The findings indicate that participants demonstrated strong conceptual mastery and were able to integrate several CRT dimensions into their instructional materials. However, limitations were identified in designing culturally responsive assessments, promoting higher-order critical thinking, and facilitating students’ active knowledge construction. Participants also experienced challenges in deeply incorporating students’ cultural backgrounds and sustaining inclusive classroom representations. These results extend CRT scholarship by highlighting gaps between theoretical understanding and instructional implementation. The study provides implications for strengthening CRT-oriented in teacher education programs and for improving the development of culturally responsive instructional materials in culturally diverse educational contexts.